2018
DOI: 10.7717/peerj.5672
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption potential of natural, pyrolysed and acid-assisted pyrolysed sugarcane bagasse for the removal of lead from contaminated water

Abstract: Lead (Pb) is a ubiquitous pollutant which poses serious threats to plants, animals and humans once entered into the food chain via contaminated industrial effluents on their discharge into the surface of water bodies and/or geological materials. This study aimed to examine and compare the biosorption potential of natural sugarcane bagasse (NB), pyrolysed sugarcane bagasse (PB) and acid assisted pyrolysed sugarcane bagasse (APB) for the removal of Pb from contaminated water. To explore this objective, a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…The application of biochar and zeolite significantly influenced greenhouse gaseous emission, soil chemical characteristics, and nutrient availability. Our results are in line with Shah et al (2018) who found that the application of zeolite-amended manure reduced NH 3 emission by about two-thirds of the manure applied to grassland. Likewise, in an experiment, wheat straw biochar addition in paddy soils reduced N 2 O emission by 42%, but there was a 12% increase in CO 2 emission ( Zhang et al, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The application of biochar and zeolite significantly influenced greenhouse gaseous emission, soil chemical characteristics, and nutrient availability. Our results are in line with Shah et al (2018) who found that the application of zeolite-amended manure reduced NH 3 emission by about two-thirds of the manure applied to grassland. Likewise, in an experiment, wheat straw biochar addition in paddy soils reduced N 2 O emission by 42%, but there was a 12% increase in CO 2 emission ( Zhang et al, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…The addition of biochar to soil tends to reduce ammonification by reducing NH 3 volatilization due to its adsorbent nature ( Gundale and DeLuca, 2006 ). It has already been proven that zeolite application can enhance N uptake, crop apparent N recovery and dry matter yield, and mitigate NH 3 volatilization ( He et al, 2002 ; Shah et al, 2018 ; Fahad et al, 2021c ).…”
Section: Discussionmentioning
confidence: 99%
“…The adsorption capacities reported by other researchers varied greatly among different adsorbents. The reason behind this variation can be different chemical composition and surface characteristics, particle size and presence of certain functional groups [21,49]. In the present work, the biochar was prepared with wheat straw, which contains significant amounts of lignin (24.1%), cellulose (32.6%) and hemicellulose (22.2%) [50].…”
Section: Comparison Of CD Sorption Capacity With Other Adsorbentsmentioning
confidence: 98%
“…The samples were taken in 10 mL plastic bottles at room temperature after 15, 30, 60, 90, 120 and 180 min of shaking. To validate the kinetic response of the Cd removal by both WSB and AWSB; pseudo-first order, pseudo-second order, intra-particle and Elovich models were employed (Equation 9) [20,21].…”
Section: Modeling Equilibrium Sorption Datamentioning
confidence: 99%
“…Peanut shells (PS) are thrown away as waste product all over the world. They are permeable and contain (hemi)cellulose material, lignin, pectin and slight amount of protein as well as a very complicated combination of polymeric organic compounds and have high electrolytic ability (Shah et al, 2018;Kocasoy & Güvener, 2009). These properties can make them effective biosorbent.…”
Section: Introductionmentioning
confidence: 99%